2020
DOI: 10.1242/dev.180646
|View full text |Cite
|
Sign up to set email alerts
|

JNK signaling is required for proper tangential migration and laminar allocation of cortical interneurons

Abstract: The precise migration of cortical interneurons is essential for the formation and function of cortical circuits, and disruptions to this key developmental process are implicated in the etiology of complex neurodevelopmental disorders, including schizophrenia, autism and epilepsy. We have recently identified the Jun N-terminal kinase (JNK) pathway as an important mediator of cortical interneuron migration in mice, regulating the proper timing of interneuron arrival into the cortical rudiment. In the current stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…However, when we analyzed nucleokinesis, the kinetics of movement were opposite: JNK-inhibited cells completed nucleokinesis at slower rates, whereas cTKO cells completed at faster rates. These data imply that cortical interneuron migration is dependent on both intrinsic and extrinsic requirements for JNK signaling, as suggested from recent in vivo and ex vivo experiments (Myers et al, 2020). While the exact mechanisms that cortical interneurons utilize to navigate their environment remain to be fully elucidated, we have found that JNK signaling exerts fine-tune control over cell biological processes required for proper interneuron migration.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, when we analyzed nucleokinesis, the kinetics of movement were opposite: JNK-inhibited cells completed nucleokinesis at slower rates, whereas cTKO cells completed at faster rates. These data imply that cortical interneuron migration is dependent on both intrinsic and extrinsic requirements for JNK signaling, as suggested from recent in vivo and ex vivo experiments (Myers et al, 2020). While the exact mechanisms that cortical interneurons utilize to navigate their environment remain to be fully elucidated, we have found that JNK signaling exerts fine-tune control over cell biological processes required for proper interneuron migration.…”
Section: Discussionsupporting
confidence: 80%
“…c-Jun NH 2 -terminal kinase (JNK) signaling is required for the initial entry of cortical interneurons into the cortical rudiment and the tangential progression of interneurons in migratory streams (Myers et al, 2020; Myers et al, 2014). In the current study, we examined the role that JNK plays in the migratory dynamics of individual interneurons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations were achieved by labelling interneurons with Green Fluorescence Protein (GFP) under control of the Distal-less Homeobox-(Dlx5/6) promoter and recording live brain slices. Jnk1 -/mice showed the most dominant effect, but double Jnk1 -/-Jnk2 -/+ and tripe conditional Jnk flox/flox Jnk2 -/-Jnk3 -/knock-out mice show exacerbated migratory defects at E13 [108,109].…”
Section: Tangential Migrationmentioning
confidence: 95%
“…Remarkably, in the late stages of development (E15), migratory defects are partially rescued by an unknown mechanism, and only cortical malformations and mispositioned interneurons are observed [108].…”
Section: Tangential Migrationmentioning
confidence: 99%